Le Rythme et la raison - Sauvanet, Pierre (Paris Kimé, 2000)
Rhythm and Reason is a philosophical approach to rhythmic phenomena. ‘Rhythmic' phenomena, that is to say not only aesthetic (poetry, music, the plastic arts, etc.), but also anthropological, biological, even cosmological... A ‘philosophical’ approach, because the question is whether, in all these fields, the same word ‘rhythm’ really means the same thing: the question is that of the relationship between the different rhythms, which must be the subject of a definition of concepts. ‘And finally, ‘approach’, because rhythm defined in this way is not an object: it remains a living phenomenon, which reason can only attempt to explain. Volume 1, Rythmologiques, contains a typology, a phenomenology and a terminology (+appendix of definitions). Volume 2, Rythmanalyses, contains aesthetic and ethical analyses (+bibliography, discography and index). (Translated with DeepL.com)
I. Rythmologiques II: Rythmanalyses
Keywords: Philosophy; Rhythm